Transformative social innovation and rural collaborative workspaces: assembling community economies in Austria and Greece [version 2; peer review: 1 approved, 3 approved with reservations] - Colm Stockdale; Vasilis Avdikos (Open Research Europe)
Background Collaborative Workspaces are rapidly growing and evolving across the world. Traditionally understood as an urban phenomenon, most research understands them as either ‘entrepreneurial-led’, as profit-driven and commercial spaces such as business incubators and accelerators, or ‘community-led’ as being bottom-up, not-for-profit ventures aimed at catering for the needs of their community. Recent years however have seen their diffusion beyond large urban agglomerations to small towns and villages, with their functions assumed to be more community-orientated. At the same time, social innovation, or social innovation processes have been gaining prominence in academia, policy, and practice, as they address societal problems and hold potential for new forms of social relations. This paper attempts to provide a novel framework towards understanding the transformative potential of rural collaborative workspaces, as they engage in processes of social innovation, by drawing from diverse and community economies literature and assemblage thinking. Methods The paper uses international case study comparison between rural Austria and Greece (One case from each country). Methods applied were: semi-structured interviews (N=28), participant observation and focus groups (2). Results Community-led rural collaborative workspaces hold transformative potential from i) their ability to assist rural actors with their capacities and realizing their desires and ii) changing individual subjectivities towards collective. Through changing social relations in praxis and perceptions, we examine how social innovation processes through collaborative workspaces can be understood as a means of opening new economic subjectivities towards creating community economies as their transformative potential. Conclusions Although rural collaborative workspaces hold potential for societal transformation, they require further institutionalization and support to move beyond the interstitial and symbiotic stages of transformation.